Adolescent Perspectives on Patient-Provider Sexual Health Communication: A Qualitative Study - Andrea J. Hoopes; Samantha K. Benson; Heather B. Howard; Diane M. Morrison; Linda K. Ko; Taraneh Shafii (SAGE Publishing, 2017)
Background: Adolescents in the United States are disproportionately affected by sexually transmitted infections and unintended pregnancy. Adolescent-centered health services may reduce barriers to health care; yet, limited research has focused on adolescents' own perspectives on patient-provider communication during a sexual health visit. Methods: Twenty-four adolescents (14-19 years old) seeking care in a public health clinic in Washington State participated in one-on-one qualitative interviews. Interviews explored participants' past experiences with medical providers and their preferences regarding provider characteristics and communication strategies. Results: Interviews revealed that (1) individual patient dynamics and (2) patient-provider interaction dynamics shape the experience during a sexual health visit. Individual patient dynamics included evolving level of maturity, autonomy, and sexual experience. Patient-provider interaction dynamics were shaped by adolescents' perceptions of providers as sources of health information who distribute valued sexual health supplies like contraception and condoms. Participant concerns about provider judgment, power differential, and lack of confidentiality also emerged as important themes. Conclusions: Adolescents demonstrate diverse and evolving needs for sexual health care and interactions with clinicians as they navigate sexual and emotional development.